2013
DOI: 10.1016/j.clineuro.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Transsphenoidal removal of huge pituitary adenomas with marked suprasellar extension: Results with modified surgical technique

Abstract: a b s t r a c tObjective: A modified transsphenoidal technique to remove huge pituitary adenomas with marked suprasellar extension (4.5-8 cm of maximum diameter) is presented. Methods:The technique allowed to avoid the occurrence of a precocious descent of the suprasellar cisternal plane into the sellar plane during tumour removal and its related consequences (incomplete tumour removal, occurrence of cerebrospinal fluid leak, prolonged time of postoperative stay in hospital). Technique is performed opening at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Considering that adenomas of this series were invasive, and of large size, our therapeutic strategy was to remove tumor as most as possible, avoiding to remove invasive tumoral component strictly connected to crucial neurovascular structures, which are often encased into the tumor; hazardous maneuvers were avoided, such as other authors reported for other benign tumors of sellar-suprasellar compartment [3]. In the cases of huge invasive adenomas with involvement of optic chiasm, A1 tracts of anterior cerebral arteries and diencephalus crossed the tumors and were not above displaced (Figures 3 and 4): we programmed a staged transsphenoidal surgery, as other authors [4], programming the second stage when the tumor remnant would had been descended into the sellar cave. In order to perform the second programmed stage, neuronavigator was employed, as previously described, because anatomical landmarks could have become unclear because of the previous operation.…”
Section: Therapeutic Strategymentioning
confidence: 91%
“…Considering that adenomas of this series were invasive, and of large size, our therapeutic strategy was to remove tumor as most as possible, avoiding to remove invasive tumoral component strictly connected to crucial neurovascular structures, which are often encased into the tumor; hazardous maneuvers were avoided, such as other authors reported for other benign tumors of sellar-suprasellar compartment [3]. In the cases of huge invasive adenomas with involvement of optic chiasm, A1 tracts of anterior cerebral arteries and diencephalus crossed the tumors and were not above displaced (Figures 3 and 4): we programmed a staged transsphenoidal surgery, as other authors [4], programming the second stage when the tumor remnant would had been descended into the sellar cave. In order to perform the second programmed stage, neuronavigator was employed, as previously described, because anatomical landmarks could have become unclear because of the previous operation.…”
Section: Therapeutic Strategymentioning
confidence: 91%